Os usos do passado e a escrita da História no De Concordantia Catholica de Nicolau de Cusa - Vieira, Thiago Henrique (2024)
The present work aims to investigate the uses of the past in Nicholas of Cusa’s argumentation in the work “De Concordantia Catholica”. The presented work was divided by its author into three parts. The first two books intended to support the reconciliation between the papacy and the church, thus fostering unity and concord within Christianity. The third book was written for a presumed reader: Emperor Sigismund of the Holy Roman Empire, with features of mirror for princes literature. The argumentation, especially in the second and third books, heavily relied on authorities from the past as models for the present. Additionally, the third book is opportune for understanding how Nicholas of Cusa worked with the relationship between past authorities and how he assessed certain documents as genuine or spurious, such as the Donation of Constantine. Throughout this book, other topics are also discussed, including the Translatio Imperii and the construction and use of the image of Byzantine Emperor Basil I as an example for Emperor Sigismund.